Risk of Injury Events in Patients With Visual Impairments: A Swedish Survey Study Among Hospital Social Workers. (September 2021) - Lundälv, Jörgen; Thodelius, Charlotta
Introduction: People with visual impairments (those who are blind or have low vision) are exposed to risks in everyday life, especially injury risks. This study aimed to examine experiences and practical knowledge among hospital social workers in Sweden concerning meetings with patients with visual impairments who have been affected by injury events in residential environments.Methods: Swedish hospital social workers specializing in patients with visual impairments ( n =30) answered a questionnaire comprising 14 questions. Both fixed and open-ended questions were included, allowing an analysis of both comparable numeric data and subjectively perceived experiences and opinions.Results: A majority of the respondents had met patients who had been injured in the residential setting; the most common injury mechanism reported was tripping or falling on the stairs, or accidentally stumbling into furniture. The hospital social workers acknowledged that they could work more preventively in their professional role by encouraging patients to use orientation and mobility devices such as long canes, increasing collaboration with other professions, and conducting home visits to enable trustful dialogues with both patients and relatives.Discussion: According to these specialized hospital social workers, the provision of education and information to patients with visual impairments could potentially prevent future injury. However, in order to achieve this, there is a need to first enable a trustful dialogue between social workers and patients.Implications for practitioners: This study provides a better understanding of the importance of trustful dialogue between hospital social workers and patients with visual impairments, from the point of view injury prevention. It also offers a summary of the knowledge of hospital social workers about risks and injury events in residential settings for patients with visual impairments.